2003
DOI: 10.1016/s0736-5748(03)00089-3
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2 family members make different contributions to cell death in hypoxia and/or hyperoxia in rat cerebral cortex

Abstract: Hypoxic brain injury during fetal or neonatal development leads to damaged immature neurons and can result in cognitive or behavioral dysfunction. Hyperoxia therapy (treatment with oxygen) is commonly applied to infants with signs of perinatal hypoxia-anoxia. Both hypoxia and hyperoxia have been shown to result in apoptosis in the brains of rats in several animal models. One determinant of cellular commitment to cell death is the differential expression of the Bcl-2 family of proteins in response to trauma. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 31 publications
4
35
0
Order By: Relevance
“…Bcl-2 is an anti-apoptotic protein present at relatively high levels in the neonatal brain and declines significantly in the postnatal brain (Abe-Dohmae et al, 1993). The expression of Bcl-2 in neonatal brain injury remains unclear (Akhtar et al, 2004;Hagberg, 2004), as several studies have shown that Bcl-2 levels may not be elevated in rodent models of neonatal brain injury (Chen et al, 2001;Northington et al, 2001), whereas others have reported contrary results (Ferrer et al, 1997;Hu et al, 2003;Nunez and McCarthy, 2004). One study reported that Bcl-2 was expressed in normal neurons, but that the expression was decreased in apoptotic neurons and further decreased in necrotic neurons following neonatal hypoxia-ischemia (Ferrer at al., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 is an anti-apoptotic protein present at relatively high levels in the neonatal brain and declines significantly in the postnatal brain (Abe-Dohmae et al, 1993). The expression of Bcl-2 in neonatal brain injury remains unclear (Akhtar et al, 2004;Hagberg, 2004), as several studies have shown that Bcl-2 levels may not be elevated in rodent models of neonatal brain injury (Chen et al, 2001;Northington et al, 2001), whereas others have reported contrary results (Ferrer et al, 1997;Hu et al, 2003;Nunez and McCarthy, 2004). One study reported that Bcl-2 was expressed in normal neurons, but that the expression was decreased in apoptotic neurons and further decreased in necrotic neurons following neonatal hypoxia-ischemia (Ferrer at al., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The animals of the HHI group were subsequently subjected to 100% oxygen for 120 min. A more detailed description of this procedure can be found elsewhere (Rice et al, 1981;Grafe, 1994Grafe, , 2008Hu et al, 2003Hu et al, , 2005Hu et al, , 2006.…”
Section: Materials and Methods Animals And Injury Modelmentioning
confidence: 99%
“…A rationale for the worsening outcome after the hyperoximic treatment was suggested by Hu et al (2003), who followed three apoptotic markers (cytoplasmic histone/DNA, caspase 3 activities, and Klenow fragments) after HI and HHI and found that hyperoximia induced an additional apoptotic pathway to the one induced by HI. Also, hyperoximia decreased CBF by 10-30% (Kety and Schmidt 1946;Rostrup et al, 1995;Watson et al, 2000;Nishimura et al, 2007;Zaharchuk et al, 2008), perhaps due to vasoconstriction (Nakajima et al, 1983;Watson et al, 2000).…”
Section: Injury After Hhimentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, this may have been due to an uncoupling of cerebral blood fl ow and cerebral oxygen consumption resulting in excess delivery of O 2 to the brain. Less marked increases in O 2 delivery to the brain have been associated with neuronal apoptosis [43,44] as well as increased lipid peroxidation indicative of free radical damage to cell membranes [45,46] . Previous studies have shown that ischemic/hypoxic brain injury in experimental animals is minimal when body temperature is allowed to decrease spontaneously but increases when the decrease in body temperature is prevented [7][8][9][10] .…”
Section: Pathophysiological Implications Of Warming Hypoxic Infantsmentioning
confidence: 99%